Supply chain management portal and its impact on supply chain performance in ministry of health and family welfare: an assessment - Roshni, Fatema Samdani (BRAC Univeristy, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2017.